Changing food preferences among a former hunter-gatherer group in Namibia - Heim, Anita; Pyhälä, Aili (Appetite, 2020)
The purpose of this study was to identify, describe and conceptualize the present drivers of food choices and preferences of the Khwe San indigenous peoples by considering influences of their historical and cultural contexts. Data were collected in Eastern Bwabwata National Park in Namibia using a range of qualitative methods: semi-structured and structured interviews and free listing. The various drivers of food choices have been clustered into four levels of the ecological conceptual framework. Key factors, found to be driving participants' food choices, were the following: taste, hunger, health, familiarity and body satisfaction at the individual level; culture and food taboos at the social level; access to food and food storage at the physical level, and; cost and seasonality at the macro level. Many of these factors are directly related to food insecurity and previous experiences of hunger. Current preferences towards traditional foods existed but were not prevailing among all the participants. Interviews with the elderly revealed the historical context of the increasing exposure to modern foods and a contested access to traditional foods and traditional knowledge transmission. Our findings exposed some substantial gaps in the nutritional knowledge of the Khwe that need consideration by future health promotion strategies along with the current perceptions of local food choices. Ensuring access and promoting sustainable management of traditional foods would not only contribute to the health of the Khwe people but also help to maintain a nutritional safety net in their current situation of extreme poverty. Peer reviewed